FAKTOR-FAKTOR YANG MEMPENGARUHI BIAYA RIIL PASIEN KEMOTERAPI KANKER PAYUDARA PESERTA JKN DI RSUD ULIN BANJARMASIN - Noor Aisyah; Saftia Aryzki; Amaliyah Wahyuni; Tri M Andayani; Diah A Puspandari (JCPS (Journal of Current Pharmaceutical Sciences), 2019)
Data from IARC in 2012 as many as 1.7 million women were diagnosed with breast cancer. Breast cancer is catastrophic, high-cost and life-threatening complications. The claim data for INA-CBGs for cancer is one of the diseases that absorbs the biggest costs. The factors that influence the real costs of breast cancer patients are length of stay, severity, class of care and age. The aim of the study was to determine the factors that affect the real costs of breast cancer chemotherapy patients hospitalized JKN participants in Ulin Banjarmasin Hospital. The study is a pharmacoeconomic analysis study with a hospital perspective on direct medical costs, data taken retrospectively. The study sample was a hospital financial file and a medical record of breast cancer patients at JKN participants for the period of January-October 2017 in Ulin Banjarmasin Hospital with 259 episodes of treatment. To find out the factors that influence the real costs using multivariate linear regression correlation analysis. The results showed that the factors that influence the real costs of chemotherapy patients in breast cancer hospitalized JKN participants in RSUD Ulin Banjarmasin were severity (p = 0,000) and treatment class (p = 0,000). The total cost of medicine from 259 episodes of care is Rp. 669,577,809, average real costs with chemotherapy treatment episodes at severity level I amounted to Rp.4,502,210, II severity level Rp.8,239,624 and III severity level Rp.7,403,713.